Preliminary Analysis Of The New Urban Agenda: The Brazil Case Study (Revista Espaço e Geografia, 2022)
The following analytical exercise wants to provide the reader with a brief introduction into the New Urban Agenda, an international guideline elaborated by UN-Habitat and agreed by all UN member countries, including Brazil. It should offer a broad overview about the context of the document, how the agenda is structured, what the principal appeals for action are, what the interconnections with other international guidelines are, how the agenda should be implemented on the regional & national level as well as what the UN-Habitat wants to achieve with it. The study will subsequently present exemplary the challenges to institutionalize the New Urban Agenda in general, and specifically in the context of Brazilian metropolitan territories through the approach in the metropolitan region of Porto Alegre/RS.